Przestępstwo publicznego propagowania faszystowskiego lub innego totalitarnego ustroju państwa art. 256 k.k.. Analiza doktrynologiczna wybranych wypowiedzi piśmiennictwai judykatury. Część szczególna I - Scheffler, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper presents interpretations of the content of art. 256 of the Polish Penal Code of 1997 The crime of public propagation of a fascist or other totalitarian governmental system, which were developed in the years 1998–2001. The most difficult problem for commentators was to understand the complexity of the phenomenon of totalitarianism and the consequences resulting from accepting one of the competing concepts of totalitarianism. Similarly, interpretational problems led to misunderstandings of the concept of fascism and the governmental system. As a result, individual authors incorrectly found resemblance between the regulations contained in the Penal Code of 1969 and the regulation contained in art. 256 from 1997.
Keywords: totalitaryzm; faszyzm; kodeks karny